2018
DOI: 10.1007/s10995-018-2531-0
|View full text |Cite|
|
Sign up to set email alerts
|

Randomized Trial of a Training Program to Improve Home Visitor Communication around Sensitive Topics

Abstract: IntroductionStrong communication skills are necessary to engage families, perform accurate assessments, and motivate behavior change around sensitive issues encountered in home visiting.MethodsA two-arm, cluster-randomized trial evaluated the impact of a trans-model communications training course for home visitors. Fourteen home visiting programs in Maryland were assigned to a training intervention (n = 7 programs; 30 visitors) or wait-list control group (n = 7 programs; 34 visitors). Independent observers ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Over 80% reported using training content more than once per week. Although these data were not compared to a control group, these favorable outcomes are consistent with a recent randomized controlled trial demonstrating that our training program improved home visitor skill in using sensitive and motivational communication techniques when discussing challenging topics such as mental health, substance use, intimate partner violence, and parenting (West et al, 2018).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Over 80% reported using training content more than once per week. Although these data were not compared to a control group, these favorable outcomes are consistent with a recent randomized controlled trial demonstrating that our training program improved home visitor skill in using sensitive and motivational communication techniques when discussing challenging topics such as mental health, substance use, intimate partner violence, and parenting (West et al, 2018).…”
Section: Discussionsupporting
confidence: 78%
“…We neither have independent verification that they did, however, nor know if their use of these skills led to greater support for home visitors. In the RCT of our program, which involved two of the four cohorts evaluated in this study, home visitors demonstrated more use of motivational communication techniques compared to controls immediately following training but then some decline in their skill use 2 months later (West et al., ). Some decline is to be expected, but it also could be that supervisor support for home visitors’ skills was not as strong as intended.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As support and enthusiasm for home visiting have grown, so too have the expectations for home visits and home visitors. It is not surprising that workforce development is a top agenda item in evidence‐based home visiting programs (Home Visiting Applied Research Collaborative, ; West et al, ). Promotion of high‐quality preservice training in higher education is one important area of home visitor workforce development.…”
mentioning
confidence: 99%
“…Both emphasize family self‐sufficiency and well‐being and share other important overlaps that position families' individual needs at the forefront of programming (Walsh, ; Walsh & Mortensen, ). Evidence‐based home visiting models, such as EHS‐HBO, require preservice and ongoing training (Sama‐Miller et al, ; West et al, ). Model‐specific training (Home Visiting Applied Research Collaborative, ; West et al) and training linked to certifications or endorsements are often supported by agencies administering home visiting programs.…”
mentioning
confidence: 99%